Investigation of the effects of pulsed ultrasound in aerated submerged culture of phellinus linteus for biomass and polysaccharide production - Nguyen Duc, Tien; Nguyen Dinh Khoa; Pham Anh Tuan; Nguyen Thi Huyen; Than Thao Nguyen; Adisak Joomwong (Vietnam Journal of Science and Technology, 2025)
Phellinus linteus is a valuable medicinal mushroom widely used in Japan and Korea, particularly for its immune-boosting and anti-tumor properties. It contains a range of chemical components, including amino acids, vitamins, minerals, carbohydrates, and bioactive compounds such as polysaccharides, protein-polysaccharides, steroids, terpenoids, and flavonoids. In Vietnam, this mushroom has become rare and costly due to its long growth cycle and overharvesting from the wild. To address this issue, submerged mycelial culture has emerged as a promising solution to reduce cultivation time while yielding extracts rich in bioactive compounds. This study explores the effect of pulsed ultrasound on the mycelial growth and polysaccharide synthesis of Phellinus linteus from Ba Be District, Bac Kan Province, Vietnam (designated as P.B91). Optimal conditions for culturing P.B91 were identified using ultrasound at a frequency of 20 kHz and an intensity of 12 W/cm² for 150 seconds, applied 108 hours post-inoculation. Ultrasonic treatment resulted in biomass yield and intracellular and extracellular polysaccharide levels of 20.73 g/L (33.96 g/L in post-culture medium), 7.14 g/L, and 5.10 g/L, respectively, representing increases of 3.34, 4.25, and 3.88 times compared to the control. These findings demonstrate the potential of ultrasonic waves in submerged culture to improve quality, reduce cultivation time, and enhance energy efficiency over traditional aerated submerged culture methods.